Penerapan Model Problem Based Learning (PBL) untuk Meningkatkan Kemampuan Pemecahan Masalah Matematis Peserta Didik Kelas VIII2 SMP Negeri 17 Pekanbaru - Subekti, Hafizah Syahrani; Murni, Atma; Siregar, Syarifah Nur (Program Studi Pendidikan Matematika Universitas Pasir Pengaraian, 2024)
This classroom action research (PTK) aimed to enhance the learning process and improve the mathematical problem-solving abilities (KPMM) of students through the implementation of the Problem-Based Learning (PBL) model. The study involved 42 students from class VIII2 of SMP Negeri 17 Pekanbaru during the even semester of the academic year 2022/2023, who varied in their academic capabilities. The research was conducted over two cycles, each consisting of four stages: planning, implementing, observing, and reflecting. Research tools included learning devices such as syllabi, lesson plans, and student worksheets, along with data collection instruments like KPMM test instruments and observation sheets. Observation data were analyzed using qualitative descriptive methods, while KPMM tests were quantitatively assessed. Qualitative analysis revealed improvements from the first to the second cycle, evidenced by increased student activity during the learning process. Quantitative analysis indicated that average KPMM test scores rose from an initial 42.61 to 64.12 in the first test and 82.53 in the second test. Consequently, the PBL model was found to significantly influence both the teaching process and the enhancement of KPMM among students, specifically in the subject of Probability.